Fatal Alveolar Echinococcosis of the Lumbar Spine - Keutgens, Aurore (American Society for Microbiology, 2013)
For the last 10 years, the southern part of Belgium has been recognized as a low-risk area of endemicity for alveolar echinococcosis. This infection, caused by Echinococcus multilocularis, usually induces a severe liver condition and can sometimes spread to other organs. However, alveolar echinococcosis involving bones has been described only very rarely. Here, a fatal case of spondylodiscitis due to E. multilocularis contracted in southern Belgium is reported.